Controlling Rotavirus-associated diarrhea: Could single-domain antibody fragments make the difference? = Hacia el control de la diarrea por rotavirus A: ¿podrían los nanoanticuerpos VHH marcar la diferencia? - Maffey, Lucia (2015)
Group A Rotavirus (RVA) remains a leading cause of severe diarrhea and child mortality. The variable domain of camelid heavy chain antibodies (VHH) display potent antigen-binding capacity, have low production costs and are suitable for oral therapies. Two sets of anti-RVA VHHs have been developed: ARP1-ARP3; 2KD1-3B2. Here, we explore the potential of both sets as a prevention strategy complementary to vaccination and a treatment option against RVA-associated diarrhea in endangered populations. Both sets have been expressed in multiple production systems, showing extensive neutralizing capacity against strains of RVA in vitro. They were also tested in the neonatal mouse model with various degrees of success in preventing or treating RVA-induced diarrhea. Interestingly, mitigation of the symptoms was also achieved with freeze-dried ARP1, so that it could be applied in areas where cold chains are difficult to maintain. 3B2 was tested in a pre-clinical trial involving gnotobiotic piglets where it conferred complete protection against RVA-induced diarrhea. ARP1 was used in the first clinical trial for anti-RVA VHHs, successfully reducing stool output in infants with RVA diarrhea, with no detected side effects.